Some aspects of land use and over population in the Ngoni Reserves of Northern Rhodesia - Hellen, J. Anthony (ERDKUNDE, 1962)
Northern Rhodesia, part of the Central African Federation, has reached a critical point in development: so far, natural economy and money economy have developed separately; in some areas the structure of tribal societies is disintegrating as able-bodied men emigrate; at the same time, the Federation's capital-intensive industry is already struggling to find enough workers at current wages. All of this calls for fundamental change or stagnation is imminent. Of the reserves of particular interest are those where the population has reached critically high numbers in relation to their primitive farming methods. Overpopulation in humans and animals causes overexploitation, this impoverishment and erosion of the soil. This essay deals with the causes of the current problems in the Ngoni reservations. Special attention is drawn to the government's countermeasures to create better farming methods, detailing the plans for smallholders and progressive villagers and the attendant difficulties in replacing tribal customs and attitudes with European ideas such as owning land and crops for sale.